A post hoc power and effect size analysis of micro-enterprise behavior: a construct measurement study of rural asnaf's entrepreneurs (RAE) development in Pahang - Rosli, Muhammad Syahrul Deen; Moidin, Shofiyyah; Mohd Arif, Mohd Izzat Amsyar; Adenan, Faezy; Abbas, Mohd Saleh; Ismail, Albert Feisal @ Muhd Feisal; Mohd Noor, Khairunneezam (ResearchTrentz Academy Publishing Education Services, 2022)
This study aims to identify the size of the impact and power required in the study of the behavior of SME entrepreneurs. Particularly it focuses on micro -entrepreneurs in remote areas in Pahang, to bridge the gap of research and look more broadly at the field of study. This study has a twostep approach, the first is to identify the constructs used by previous researchers in the study of entrepreneurship and training course and conducted a field survey of RAE through random sampling technic. The findings of this study were analyzed with validity and reliability of data values through alpha and R-squared value. After obtaining reliable validity and R-Square values, power analysis (1-β) and effect size (F2) were identified and analyzed with G*Power software. The findings of the study found that the high value of R-square caused sufficient power (1- β = 0.80) to be achieved at the 20th sampling (n = 20). The results of this study also support the findings of Connelly et al (2010) who suggested that power studies on entrepreneurial behavior are higher than expected. However, F2 of this study is lower than that proposed by Connelly et al (2010) for micro and medium enterprises at the rate of F2 = 0.9 only compared to 0.14 - 0.25. This initial study can be a benchmark to the value of impact size and power to subsequent studies in the field of entrepreneurship, however, it has limitations only on rural asnaf entrepreneurs. Further studies can be made of entrepreneurs in other fields, with more universal constructs as well as other theoretical frameworks.